ANALYSIS OF FACTORS AFFECTING CAPITAL ADEQUACY RATIO BETWEEN ISLAMIC BANK AND CONVENTIONAL BANK CASE STUDY – MANDIRI SYARIAH AND MANDIRI (2009-2016) - Kasmadi, Kartika Aprillia; Lambey, Linda .; Tumiwa, Johan . (Universitas Sam Ratulangi, 2017)
Abstract : Banks are expected to perform their activities effectively and efficiently in order to reach financial goals. A healthy standard for banks in Indonesia is determined by Central Bank (Bank Indonesia), which is above 8% for the indication of capital adequacy ratio. This research analyses the relationship between capital adequacy ratio and its determinants between Mandiri and Mandiri Syariah bank. This research examines the simultaneous and partial influences between capital adequacy ratio and the variables of return on equity, net interest margin, loan/financing to deposit ratio, and bank size by using time series regression and using the quarterly period of 2009-2016.Â The results reveal that the independent variables simultaneously affect capital adequacy ratio for both banks, and by partially, the results confirm that return on equity and bank size significantly affect capital adequacy ratio. With this research, companies are encouraged to figure out the root problems on how to manage a stable financial statements that may lay on some of the variables that are discussed in this study.Keywords : capital adequacy ratio, return on equity, loan to deposit ratio, financing to deposit ratio, bank size.e